Estimation of the ideal dietary essential amino acid pattern for pacu (Piaractus mesopotamicus) in the later-juvenile growth phase - Rodrigues, Andressa Tellechea [UNESP]; Mansano, Cleber Fernando Menegasso; Khan, Kifayat Ullah [UNESP]; Nascimento, Thiago Matias Torres do [UNESP]; Santos, Monique Virães Barbosa dos [UNESP]; Sakomura, Nilva Kazue [UNESP]; Fernandes, João Batista Kochenborger [UNESP] (Elsevier, 2022)
This study aimed to estimate the ideal pattern of dietary essential amino acids (EAAs) for pacu (Piaractus mesopotamicus) in the later-juvenile growth phase (weighing 460–560 g) by the amino acid (AA) deletion method. A total of 231 pacu in the later-juvenile growth phase (with initial average body weight of 460 ± 4.65 g) were equally distributed in a completely randomized design among 33 fiber tanks of 1000-L (7 fish per tank) in a closed water recirculation system. The trial consisted of 11 treatments including a control diet (CD) and 10 EAA-deficient diets (DDs), with three replicates (tanks) per treatment. The CD consisted of 45% synthetic amino acids and purified feed ingredients and 55% non-purified conventional feed ingredients. The 10 DDs represented the same nutritional composition of the CD but each DD was maintained deficient in 45% of the respective test EAA. During the 60-day experimental duration, fish were fed with extruded diets three times a day until apparent satiation. The present results revealed that fish fed with CD showed better growth performance, feed utilization and body N deposition as compared to DDs. The ideal pattern of dietary EAAs was estimated through the relationship between body nitrogen retention and the amount of amino acid deleted from the control diet. Based on the deletion method, the ideal pattern of dietary EAAs for pacu in the later-juvenile growth phase (expressed relative to lysine requirement of 100%) was estimated as: arginine (84.33%); phenylalanine (55.21%); histidine (29.52%); isoleucine (55.06%); leucine (73.82%); methionine (24.86%); threonine (46.08%); tryptophan (10.42%); and valine (57.00%).
Keywords: Amino acid nutrition; Deletion method; Fish; Growth performance; Ideal EAA profile; Nitrogen retention